Positron emission tomography for phenotyping inflammation of cardiovascular diseases - Xiaoyun Luo; Chentao Jin; Hetian Chen; Xiaohui Zhang; Yan Zhong; Peili Cen; Hong Zhang; Mei Tian (EngMedicine)
Inflammatory processes play a central role in the development and complications of cardiovascular diseases (CVDs), profoundly affecting the severity and prognosis of these events. However, the current tools used to measure inflammation have some limitations. Blood biomarkers cannot pinpoint the location of inflammation and are vulnerable to various factors. Histological assessments ex vivo cannot accurately reflect the full dynamic picture of pathophysiology. The rapid development of positron emission tomography (PET) imaging not only enhances our understanding of biological processes in vivo but also contributes significantly to clinical management as a non-invasive biomarker. This review summarizes the PET imaging of key immune cell responses in CVDs, including immune cell metabolism, ligand/receptor interactions, and enzyme secretion, and discusses emerging opportunities and challenges in PET imaging-based inflammatory phenotyping and future perspectives.